Strategi Promosi Berbasis Branding, Advertising, Selling (BAS) dalam Industri Pariwista Kecamatan Talun Kabupaten Cirebon - Sudiana Wachyudi; Annisaa Eka Warliati; Jasmine Callysta Setiawan (STIKes Ibnu Sina Ajibarang, 2024)
The importance of branding, advertising and selling (BAS) for both tourist attractions and government agencies, one of which is to be able to improve the image and reputation of a tourist attraction or agency so that it can be known by the wider community. Likewise in the tourism sector, the existence of the BAS concept in addition to being able to change and improve the image of the region, advertising activities will have a great impact on the tourism sector such as being able to attract tourists, investors, be known by the public, and increase the number of tourist visits. In the context of tourism marketing, BAS strategy, especially in terms of advertising, plays a decisive role in achieving the goal, namely the accuracy of marketing promotion actions to reach the specified market segment. This can be seen, among other things, from the increase in the number of tourists who buy tourism products or visit marketed destinations. The researcher uses a qualitative descriptive approach because in accordance with the purpose of the research, namely wanting to obtain and describe in depth and thoroughly the BAS promotion strategy in terms of advertising in the development of the tourism industry in Talun District, Cirebon Regency as a tourist destination. Advertising/Advertising in tourist destinations carried out by the Talun District government through social media is very effective and efficient in saving marketing budgets. This program increases public interest in various tourist attractions that can be visited through videos containing natural beauty, tourist attractions, culinary places and information related to the calendar of activities in Talun District which is then uploaded through the website and social media Instagram, blogs, Facebook, and Youtube.